FEKTIVITAS PENERAPAN APLIKASI SIREFKA (SISTEM INFORMASI REALISASI FISIK DAN KEUANGAN) TERHADAP PELAKSANAAN MONITORING DAN EVALUASI DI PEMERINTAH KOTA JAYAPURA. - Henrlizth; Lamba, Arung; Bahtiar, Petrus (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2025)
This research aims to identify the factors influencing the growth of settlements and economic activities in Koya BaratVillage, Muara Tami District, and the efforts made in the growth of settlements and economic activities in Koya BaratVillage, Muara Tami District. The quantitative research method and data collection techniques involve questionnairesand documentation. The data analysis uses simple linear regression. The results of the research indicate that thefactors influencing the growth of settlements and economic activities in Koya Barat Village, Muara Tami District, showthat the level of settlement growth in Koya Barat Village, Muara Tami District, is categorized as high, with 65respondents or 65%. This includes several factors such as the type of physical building, building/occupant type, walltype, roof type, ceiling, floor type, door, sanitation, window, ventilation, and ridge. The economic level of thecommunity with a very high economic level is 33 respondents or 33%, and a high economic level is 31 respondents or31%, which means that the economic level of the community in Koya Barat Village, Muara Tami District is high,including education level, occupation/livelihood, and household income. The efforts made in the growth ofsettlements and economic activities in Koya Barat Village, Muara Tami District, indicate a significant influence ofsettlement growth on the economy in Koya Barat Village, Muara Tami District, which means that if settlement growthincreases, economic activities will also experience a significant increase.